2016
DOI: 10.3109/21678421.2016.1148170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a novel cervical orthosis, the Sheffield Support Snood, in patients with amyotrophic lateral sclerosis/motor neuron disease with neck weakness

Abstract: Objective Current practice and guidelines recommend the use of neck orthoses for people with amyotrophic lateral sclerosis (ALS) to compensate for neck weakness and to provide surrogate neck control. However, available options are frequently described by patients as restrictive and unsuitable and there was a need for a new device that addressed the needs of people with ALS. MethodsThis project utilised a co-design process to develop a new neck orthosis that was more flexible yet supportive. Following developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…Es kommen abhängig vom klinischen Bild diverse Orthesen zum Einsatz, mittels derer eine Schmerzkontrolle, Kontrakturprophyla xe und Zunahme der Selbständigkeit erzielt werden kann [37]. Pu bliziert wurde der erfolgreiche Einsatz von Handorthesen [37,38,39], UnterschenkelFußOrthesen [15,40] und Halsorthesen bei Schwäche der Nackenmuskulatur [41,42], allerdings profitieren nicht alle Patienten von einer Orthese [43]. Wichtig ist der Ein satz zum richtigen Zeitpunkt, um einen optimalen Effekt auf die Aktivitäten des täglichen Lebens und die Lebensqualität zu erzie len [38,39].…”
Section: Orthesen Und Prothesenunclassified
“…Es kommen abhängig vom klinischen Bild diverse Orthesen zum Einsatz, mittels derer eine Schmerzkontrolle, Kontrakturprophyla xe und Zunahme der Selbständigkeit erzielt werden kann [37]. Pu bliziert wurde der erfolgreiche Einsatz von Handorthesen [37,38,39], UnterschenkelFußOrthesen [15,40] und Halsorthesen bei Schwäche der Nackenmuskulatur [41,42], allerdings profitieren nicht alle Patienten von einer Orthese [43]. Wichtig ist der Ein satz zum richtigen Zeitpunkt, um einen optimalen Effekt auf die Aktivitäten des täglichen Lebens und die Lebensqualität zu erzie len [38,39].…”
Section: Orthesen Und Prothesenunclassified
“…Dialogue with our patient participants in our co-design team indicated that the neck orthosis given to MND patients were worn as little as possible, with 20-30 minute periods being cited by some although greater time frames being cited by others. This view from MND patients was formally captured in a later evaluation (Baxter et al 2016) with a wider, external group of MND patients.…”
Section: Limitationsmentioning
confidence: 99%
“…After successful completion and evaluation in healthy participants (11), the HeadUp collar was assessed in people living with ALS, using a mixed methods cohort study (12). Twenty patients with both ALS and neck weakness (who had also tried other neck orthoses) were recruited and fitted with the HeadUp collar.…”
Section: Introductionmentioning
confidence: 99%